TRANSLATING GEOGRAPHICAL NAMES: PHONETIC VS SEMANTIC TRANSLATION. (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta'limning o'rni hamda rivojlanish omillari, 2025)
Abstract: This paper examines the contrast between phonetic and semantic translation in the context of geographical terms by highlighting the need for a balanced approach, linguistic characteristics of the target language.